EFEK KOMBINASI MAGNESIUM SULFAT (MGSO4) DAN NIFEDIPINE TERHADAP PENURUNAN TEKANAN DARAH PADA KASUS PREEKLAMPSIA BERAT DI RSPAD GATOT SOEBROTO TAHUN 2021-2022 - Bunga Mentari Rizkyta, Bunga (2023)
dying in 2021. One of the causes of the high MMR is the presence of hypertension in pregnancy, called preeclampsia. Preeclampsia still affects 10% of pregnant women worldwide, and the COVID-19 pandemic makes it difficult to diagnose preeclampsia. To reduce mortality due to preeclampsia, generally pregnant women receive antihypertensive treatment such as MgSO4 or nifedipine. However, it is necessary to know further whether the combination of MgSO4 with nifedipine can reduce blood pressure in pregnant women with preeclampsia and eclampsia. This study uses a descriptive analytic research design with a cross sectional approach. Subjects were medical records of preeclampsia patients at the the RSPAD Gatot Soebroto and were obtained based on inclusion and exclusion criteria. Sampling using total sampling technique. The data obtained was then analyzed univariately such as patient characteristics, as well as bivariately to see a comparison of the decrease in blood pressure after 24 hours and the end of treatment. The data obtained were 58 patients, and after being selected based on inclusion and exclusion criteria, 30 patients were found to be used. The results of the chi square test at 24 hours after administration of the combination of MgSO4 and nifedipine obtained a p-value of 0.193 and at the end of treatment obtained a p-value of 0.091. Both of these results showed that there was no difference in blood pressure reduction in the mild-moderate or severe groups when given nifedipine and MgSO4. It can be concluded that there is no significant difference between the decrease in blood pressure to normal values in the mild-moderate and severe blood pressure groups after administration of nifedipine and MgSO4 at the RSPAD Gatot Soebroto. Keywords: Blood Pressure, Magnesium Sulfate, Nifedipine, Severe Preeclampsia.